2010
DOI: 10.1186/1743-0003-7-50
|View full text |Cite
|
Sign up to set email alerts
|

Fall prevention and vitamin D in the elderly: an overview of the key role of the non-bone effects

Abstract: Preventing falls and fall-related fractures in the elderly is an objective yet to be reached. There is increasing evidence that a supplementation of vitamin D and/or of calcium may reduce the fall and fracture rates. A vitamin D-calcium supplement appears to have a high potential due to its simple application and its low cost. However, published studies have shown conflicting results as some studies failed to show any effect, while others reported a significant decrease of falls and fractures. Through a 15-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
90
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 124 publications
(219 reference statements)
3
90
0
6
Order By: Relevance
“…It is the case that 25(OH)D was shown to predict lower-extremity function in both active and inactive persons aged ‡ 60 years (74) and a meta analysis of RCT of vitamin D supplementation showed a > 20% reduced risk of falls among ambulatory or institutionalised elders (75) . Furthermore, the more recent suggestion in a systematic review that the association between vitamin D and physical performance remains controversial (76) appeared to be resolved by an updated meta analysis of RCT in which studies were separated according to intervention dose (77) . This showed that supplemental vitamin D reduced the risk of falling among older individuals by 19% for interventions ‡ 17 .…”
Section: Vitamin D: Strength Preservation In Musclementioning
confidence: 99%
“…It is the case that 25(OH)D was shown to predict lower-extremity function in both active and inactive persons aged ‡ 60 years (74) and a meta analysis of RCT of vitamin D supplementation showed a > 20% reduced risk of falls among ambulatory or institutionalised elders (75) . Furthermore, the more recent suggestion in a systematic review that the association between vitamin D and physical performance remains controversial (76) appeared to be resolved by an updated meta analysis of RCT in which studies were separated according to intervention dose (77) . This showed that supplemental vitamin D reduced the risk of falling among older individuals by 19% for interventions ‡ 17 .…”
Section: Vitamin D: Strength Preservation In Musclementioning
confidence: 99%
“…(14) Supplementation of vitamin D has been shown to improve relative muscle fiber composition and fibers area of type IIa muscle fibers, and has also been reported to have an effect on antigravity muscles, supported by the improvement in postural equilibrium tests. (11) Although there is no consensus of which vitamin D level is defined as deficient, (15) it has been suggested that serum vitamin D level should be at least 75 nmol/L, which implies numerous elderly in the community and LTC facilities would be deficient in Vitamin D, thus supplementation would be warranted. (16) It is a safe supplement to prescribe without significant adverse effects prescribed at standard doses or supratherapeutic doses.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D can also be obtained through diet, which consists of cholecalciferol and ergocalciferol (vitamin D 2 (10) A recent review has suggested histological and interventional evidence between vitamin D deficiency and muscle weaknesses. (11) Severe vitamin D deficiency to the extent of osteomalacia causes proximal and lower limb muscle weaknesses, with histological evidence of predominant type II muscle atrophy, widening of interfibrillary spaces, fatty infiltration, fibrosis, and the presence of glycogen granules without signs of inflammatory reaction. In less extreme cases, 30% of muscle biopsies revealed features of vitamin D insufficiency-related myopathies.…”
Section: Introductionmentioning
confidence: 99%
“…9 Vitamin D supplementation reduces the risk of falls in older adults through effects on muscle and the nervous system (both central and peripheral), whereby it improves gait and balance. 8,10 Vitamin D supplementation of > 800 IU per day, aiming to achieve 25(OH)D levels of at least 30 ng/ml, was somewhat favourable in preventing hip fractures and nonvertebral fractures in persons who were 65 years and older. 11 …”
Section: Skeletal Healthmentioning
confidence: 99%